2022
DOI: 10.1242/dev.200252
|View full text |Cite
|
Sign up to set email alerts
|

Functions of the FGF signalling pathway in cephalochordates provide insight into the evolution of the prechordal plate

Abstract: The fibroblast growth factor (FGF) signalling pathway plays various roles during vertebrate embryogenesis, from mesoderm formation to brain patterning. This diversity of functions relies on the fact that vertebrates possess the largest FGF gene complement among metazoans. In the cephalochordate amphioxus, which belongs to the chordate clade together with vertebrates and tunicates, we have previously shown that the main role of FGF during early development is the control of rostral somite formation. Inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 80 publications
4
11
0
Order By: Relevance
“…Therefore, metacell 1 represents a potential prechordal plate-like territory showing a transcriptomic profile characterized by anterior and axial markers together with endodermal markers. Such a territory was already proposed to exist in amphioxus based on both cell behaviour and gene expression of several marker genes 12,17,79 but our data highlight the strong difference in its transcriptomic profile compared to the other notochord cells, reinforcing the idea that ancestral chordates possessed a prechordal plate-like region that later evolved specific functions in vertebrates.…”
Section: Resultssupporting
confidence: 74%
See 2 more Smart Citations
“…Therefore, metacell 1 represents a potential prechordal plate-like territory showing a transcriptomic profile characterized by anterior and axial markers together with endodermal markers. Such a territory was already proposed to exist in amphioxus based on both cell behaviour and gene expression of several marker genes 12,17,79 but our data highlight the strong difference in its transcriptomic profile compared to the other notochord cells, reinforcing the idea that ancestral chordates possessed a prechordal plate-like region that later evolved specific functions in vertebrates.…”
Section: Resultssupporting
confidence: 74%
“…4c, d ). The first somite pair in amphioxus has long been proposed as being distinct from the other pairs, and we previously showed that this somite pair is the only one whose formation is controlled by the FGF signalling pathway 11,12,54 . Our molecular atlas additionally shows that the cells of the first pair of somites transcriptionally resemble vertebrate head and lateral plate mesoderm (metacells 1 and 3, Fig.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…The embryo imaged at the late neurula stage showed expression in the ventral epidermis and in the somites ( Fig 2 ). The same protocol was succesfully undertaken to trace the fate of the presumptive anterior somite territory in embryos in which the FGF signalling pathway was inhibited by using a FGFR inhibitor (SU5402) as published in [ 12 ].…”
Section: Expected Resultsmentioning
confidence: 99%
“…territory in embryos in which the FGF signalling pathway was inhibited by using a FGFR inhibitor (SU5402) as published in [12].…”
Section: Plos Onementioning
confidence: 99%